1989
DOI: 10.1038/bjc.1989.303
|View full text |Cite
|
Sign up to set email alerts
|

c-erbB-2/c-erbA co-amplification indicative of lymph node metastasis, and c-myc amplification of high tumour grade, in human breast carcinoma

Abstract: Summary A panel of 73 samples, including 52 primary breast carcinomas, 10 normal breast tissues and 11 axillary lymph nodes, has been analysed for the presence of amplifications and gross structural alterations, in the oncogenes c-erbB-2, c-erbA, c-myc, N-myc, c-mos and c-Ha-ras. The tumours were also classified, graded and staged histopathologically and their DNA ploidy (42 samples) was determined by flow cytometry. Three breast cancer cell lines (MCF7, ZR-75-1 and T47D) were also included in the study. Ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 32 publications
3
19
0
Order By: Relevance
“…The analysis included 29 reports (representing 26 distinct studies) that met the inclusion criteria. Twenty-six of the 29 reports were included in the estimation of the overall proportion of c-myc-amplified tumors (Escot et al, 1986;Cline et al, 1987;Varley et al, 1987;Bonilla et al, 1988;Guerin et al, 1988;Adnane et al, 1989;Garcia et al, 1989;Tavassoli et al, 1989;Tsuda et al, 1989;Zhou et al, 1989;Brouillet et al, 1990;Meyers et al, 1990;Munzel et al, 1991;Berns et al, 1992b;Borg et al, 1992;Roux-Dosseto et al, 1992;Kreipe et al, 1993;Nagayama and Watatani, 1993;Ottestad et al, 1993;Scorilas et al, 1993;Watson et al, 1996;Yamashita et al, 1993;Bieche et al, 1994;Harada et al, 1994;Contegiacomo et al, 1995;Lonn et al, 1995). Amplification data in Champeme et al (1994), Scorilas et al (1995) and Berns et al (1992) were excluded from estimation of the overall proportion, since they were originally reported in Bieche et al (1994), Scorilas et al (1993) and Berns et al (1992b), respectively.…”
Section: Results Of Citation Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis included 29 reports (representing 26 distinct studies) that met the inclusion criteria. Twenty-six of the 29 reports were included in the estimation of the overall proportion of c-myc-amplified tumors (Escot et al, 1986;Cline et al, 1987;Varley et al, 1987;Bonilla et al, 1988;Guerin et al, 1988;Adnane et al, 1989;Garcia et al, 1989;Tavassoli et al, 1989;Tsuda et al, 1989;Zhou et al, 1989;Brouillet et al, 1990;Meyers et al, 1990;Munzel et al, 1991;Berns et al, 1992b;Borg et al, 1992;Roux-Dosseto et al, 1992;Kreipe et al, 1993;Nagayama and Watatani, 1993;Ottestad et al, 1993;Scorilas et al, 1993;Watson et al, 1996;Yamashita et al, 1993;Bieche et al, 1994;Harada et al, 1994;Contegiacomo et al, 1995;Lonn et al, 1995). Amplification data in Champeme et al (1994), Scorilas et al (1995) and Berns et al (1992) were excluded from estimation of the overall proportion, since they were originally reported in Bieche et al (1994), Scorilas et al (1993) and Berns et al (1992b), respectively.…”
Section: Results Of Citation Searchmentioning
confidence: 99%
“…Seven prognostic factors were analysed for their association with c-myc amplification: lymph node involvement (Escot et al, 1986;Cline et al, 1987;Varley et al, 1987;Adnane et al, 1989;Tavassoli et al, 1989;Berns et al, 1992a;Borg et al, 1992;Kreipe et al, 1993;Nagayama and Watatani, 1993;Scorilas et al, 1993;Champeme et al, 1994;Harada et al, 1994;Lonn et al, 1995), oestrogen receptor status (Escot et al, 1986;Varley et al, 1987;Adnane et al, 1989;Garcia et al, 1989;Berns et al, 1992b;Borg et al, 1992;Kreipe et al, 1993;Yamashita et al, 1993), progesterone receptor status (Escot et al, 1986;Adnane et al, 1989;Garcia et al, 1989;Berns et al, 1992b;Borg et al, 1992;Kreipe et al, 1993;Champeme et al, 1994), age (Escot et al, 1986;Guerin et al, 1988;Adnane et al, 1989;Berns et al, 1992a;Borg et al, 1992;Kreipe et al, 1993), menopausal status (Varley et al, 1987;Berns et al, 1992a;Borg et al, 1992;Yamashita et al, 1993), tumour size (Guerin et al, 1988;Adnane et al, 1989;…”
Section: Results Of Citation Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were refuted by others (Ali et al, 1988;Zhou et al, 1989). Gene amplification of c-erbB-2 correlated with lymphnode involvement (Slamon et al, 1987;Zhou et al, 1987;Slamon et al, 1989;Guerin et al, 1989;Tavassoli et al, 1989), histological grade (Berger et al, 1988;Tavassoli et al, 1989;Tsuda et al, 1989, Paik et al, 1990, negative ERcontent Guerin et al, 1989;Zeillinger et al, 1989;Heintz et al, 1990), early recurrence (Zhou et al, 1987;Cline et al, 1987;Varley et al, 1987), short overall survival time Slamon et al, 1987;Varley et al, 1987;Slamon et al, 1989;Paik et al, 1990) and increased mitotic activity (Heintz et al, 1990;Ramachandra et al, 1990). All of these factors are considered to be bad prognostic indicators.…”
mentioning
confidence: 99%
“…These frequencies have, however, not been confirmed by other investigators (17,29,30). Although some studies have demonstrated a higher rate of c-myc amplification in node-positive than in node-negative primary tumours, a clear relationship between c-myc amplification and aggressive disease behaviour has not been demonstrated (25,31,32).…”
mentioning
confidence: 99%